E-Tourism Kota Tomohon Menggunakan HTML5 - Harsda Mangkey; Yaulie D.Y. Rindengan; Virginia Tulenan (Jurnal Teknik Elektro dan Komputer, 2016)
ABSTRACT E-tourism of Tomohon City intended to collect, store and manage data associated with the church members, priests, and religion teachers in the Evangelical Christian Church in Minahasa. Process and system design activity refers to the agile approach to Disciplined Agile Delivery (DAD) methodology. System modeling using UML 2.0. The system is developed based on web, system development using HTML5, PHP, Javascript, and MySQL. ABSTRAK E-tourism Kota Tomohon ini dimaksudkan sebagai sarana mengakses informasi serta tempat untuk mengelola data mengenai objek dan event wisata di Kota Tomohon. Panduan proses dan aktivitas perancangan sistem ini mengacu pada pendekatan agile dengan metodologi Disciplined Agile Delivery (DAD). Pemodelan sistem menggunakan UML 2.0. Sistem dikembangkan berbasis web, pengembangan sistem menggunakan HTML5, CSS3, PHP, Javascript, dan MySQL. Kata kunci: CSS3, Disciplined Agile Delivery, E-tourism, HTML5, Javascript, MySQL, PHP, UML, Web.